Building Teacher Self-Efficacy to Improve Student Literacy - Klak, Travis (Scholarship@Western, 2019)
Literacy rates in schools across Nunavut has been a prevalent issue in recent years. Students are graduating with lower literacy levels than in many other parts of Canada. More specifically, the school in which I work also suffers from this issue. This organizational improvement plan has a problem of practice at its core that probes how current research can assist me, as principal, in supporting teachers to more effectively implement a balanced literacy program throughout my school for the purpose of improving students’ literacy levels in both of the community’s languages – English and Inuktitut. In order to address this gap in literacy skills, a comprehensive strategy is devised to be implemented aligning with best practices in literacy instruction. A distributed leadership approach will be used to collaboratively lead school staff towards effective execution of this plan utilizing Kotter’s 8 step Change Path model. Initial stages of this plan center on developing a shared vision of literacy in the school, and then reading skills, and writing skills at the K-9 level. Future considerations to this organizational improvement plan include foci on improving parental engagement with the school, and on writing skills at the high school level. Training for some aspects of balanced literacy has been conducted in previous years, however effective implementation has not been conducted in the past, thus the primary challenge of plan implementation is garnering staff support with this strategy. Keywords: Distributed Leadership, Shared Vision, Balanced Literacy, Teacher Efficacy.